THE CYCLE LENGTH OF SPARSE REGULAR GRAPH - Christy, Claudia; Suwilo, Saib; Tulus, Tulus (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Let be a reguler graph with girth . Set of cycle length in Graf is denoted by . Graph is a sparse graph if and only if . Furthermore, it was obtained the number of cycle length of sparse reguler graph which denoted is .